Fecundability and parental exposure to ambient sulfur dioxide - Dejmek, J; Jelínek, R; Solansky', I; Benes, I; Srám, R J (Environmental health perspectives, 2000)
Recently it has been observed that birth rates in Teplice, a highly polluted district in Northern Bohemia, have been reduced during periods when sulfur dioxide levels were high. This study, which is based on data from 2,585 parental pairs in the same region, describes an analysis of the impact of SO(2) on fecundability in the first unprotected menstrual cycle (FUMC). We obtained detailed personal data, including time-to-pregnancy information, via maternal questionnaires at delivery. We estimated individual exposures to SO(2) in each of the 4 months before conception on the basis of continual central monitoring. Three concentration intervals were introduced: < 40 microg/m(3 )(reference level); 40-80 microg/m(3); and [greater than or equal to] 80 microg/m(3). We estimated adjusted odds ratios (AORs) of conception in the FUMC using logistic regression models. Many variables were screened for confounding. AORs for conception in the FUMC were consistently reduced only for couples exposed in the second month before conception to SO(2) levels as follows: 40-80 microg/m(3), AOR 0.57 [95% confidence interval (CI), 0.37-0.88; p < 0.011]; [greater than or equal to] 80 microg/m(3), AOR 0.49 (CI, 0.29-0.81; p < 0.006). The association was weaker in the second 2 years of the study, probably due to the gradual decrease of SO(2) levels in the region. The relationship between SO(2) and fecundability was greater in couples living close to the central monitoring station (within 3.5 km). The timing of these effects is consistent with the period of sperm maturation. This is in agreement with recent findings; sperm abnormalities originating during spermatid maturation were found in young men from Teplice region who were exposed to the increased levels of ambient SO(2). Alternative explanations of our results are also possible.
Keywords: Fertility; Male; Middle Aged; Adolescent; Pregnancy; těhotenství; Adult; Spermatozoa; výsledek těhotenství; dospělí; mužské pohlaví; Paternal Exposure; mladiství; látky znečišťující vzduch; fertilita; Pregnancy Outcome; lidé; ženské pohlaví; Humans; matka - expozice noxám; Environmental Exposure; Maternal Exposure; spermie; zrání spermie; oxid siřičitý; Sulfur Dioxide; Female; Sperm Maturation; lidé středního věku; vystavení vlivu životního prostředí; otec - expozice noxám; Air Pollutants